Test-Retest Reliability and Validity Results of the Youth Physical Activity Supports Questionnaire. (19th May 2015) - Slater, Sandy; Full, Kelsie; Fitzgibbon, Marian; Uskali, Amber
As youth obesity rates remain at unacceptably high levels, particularly across underserved populations, the promotion of physical activity has become a focus of youth obesity prevention across the United States. Thus, the purpose of this study was to develop and test the reliability and validity of a self-reported questionnaire on home, school, and neighborhood physical activity environments for youth located in low-income urban minority neighborhoods and rural areas. Third-, fourth-, and fifth-grade students and their parents were recruited from six purposively selected elementary schools (three urban and three rural). A total of 205 parent/child dyads completed two waves of a 160-item take-home survey. Test-retest reliability was calculated for the student survey and validity was determined through a combination of parental and school administrator responses, and environmental audits. The majority (90%) of measures had good reliability and validity (74%; defined as ≥70% agreement). These measures collected information on the presence of electronic and play equipment in youth participants' bedrooms and homes, and outdoor play equipment at schools, as well as who youth are active with, and what people close to them think about being active. Measures that consistently had poor reliability and validity (≤70% agreement) were weekly activities youth participated in and household rules. Principal components analysis was also used to identify 11 sub-scales. This survey can be used to help identify opportunities and develop strategies to encourage underserved youth to be more physically active.